A new number field construction of the lattice E8 - Flores, André Luiz; Interlando, J.Carmelo; da Nóbrega Neto, Trajano Pires [UNESP]; Contiero, André Luís (Springer Nature, 2013)
Known number theoretical constructions of the lattice E8 use the cyclotomic fields Q(ζ15), Q(ζ20), and Q(ζ24). In this work, an infinite family of Abelian number fields yielding rotated versions of the lattice E 8 is exhibited. © 2012 The Managing Editors.
Keywords: Cyclotomic fields; Geometry of numbers; Lattices; Quadratic forms; Sphere packings